Always Poor or Never Poor and Nothing in Between? Duration of Child Poverty in Germany - Michael Fertig; Marcus Tamm (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2007)
This paper analyses the duration of child poverty in Germany. In our sample, we observe the entire income history from the individuals? birth to their coming of age at age 18.Therefore we are able to analyze dynamics in and out of poverty for the entire population of children, whether they become poor at least once or not. Using duration models,we allow poverty exit and re-entry to be correlated even after controlling for observable characteristics and also account for correlations with initial conditions. Our results indicate that household composition, most importantly single parenthood, and the labour market status as well as level of education of the household head are the main driving forces behind exit from and re-entry into poverty and thus determine the (long-term) experience of child poverty. However, unobserved heterogeneity seems to play an important role as well.
Keywords: C41; I32; D31; 330; Child poverty; duration analysis; unobserved heterogeneity; Kinder; Armut; Statistische Bestandsanalyse; Soziale Mobilität; Deutschland